Strength and deformation behaviors of bedded rock mass under bolt reinforcement - Zhu, Wenxin; Jing, Hongwen; Yang, Lijun; Pan, Bing; Su, Haijian (International journal of mining science and technology, 2018)
The mechanism of bolt support is an important topic in mining engineering and slope treatment. The artificial material and loading system were self-developed to study the influence of bedding cohesion and bolt number on the anchoring behavior of bedded rock mass. The results show that, both peak strength and elasticity modulus increase gradually with the increase of bedding cohesion and bolt number. The axial stress–strain curve of bedded rock mass under the reinforcement of bolts presents the features of strain-softening and secondary strengthening. Finally, anchoring behavior of bedded rock mass with different bolt numbers was simulated by using FLAC3D numerical program and the results were compared with the experimental results. This study can provide certain bases to the stability control and support design of bedded rock mass in roadway.